Building on a construct : the Adolpho Leirner collection of Brazilian constructive art at the Museum of Fine Arts, Houston - Museum of Fine Arts, Houston; Olea, Héctor; Ramírez, Mari Carmen, 1955-; Haus Konstruktiv (Zurich, Switzerland); Exhibition Zürich, Haus Konstruktiv 2009-11,18 (Houston : Museum of Fine Arts ; New Haven [Conn.] : Distributed by Yale University Press, 2009)
"Focusing on the acclaimed Adolpho Leirner Collection of Brazilian Constructive Art, this book assesses the state of research on the avant-garde artists and groups that constituted Brazilian Modernism"--Provided by publisher.
Issued in connection with an exhibition held Nov. 18, 2009-Mar. 2010, Haus Konstruktiv, Zurich, Switzerland.
Includes bibliographical references and index.
boek